Assessing the Impact of Obesity on Pregnancy and Neonatal Outcomes among Saudi Women - Nadia Adwani; Howieda Fouly; Tagwa Omer (MDPI AG, 2021)
Background: The rising prevalence of obesity has a significant impact on obstetrics practice regarding maternal and perinatal complications includes recurrent miscarriage, pregnancy-induced hypertension, preeclampsia, gestational diabetes, and prolonged labor. Objective: To assess the impact of obesity on pregnancy and neonatal outcomes among Saudi women. Methods: The study was conducted at King Abdul-Aziz Medical City, Jeddah. Design: A cross-sectional retrospective design. A total number of 186 participants were recruited from July to December 2018 according to eligibility criteria. The data were collected retrospectively by a review of the chart records of the labor and delivery department. Results: The mean (SD) age of participants was 31.94 (5.67) years old; two-thirds were in obesity class I. There was a significant association between obesity and pre-existing thyroid disease and induced hypertension class III. However, episiotomy showed that obesity class III was significantly different from obesity class II. Conclusion: This study concludes obesity affects the outcomes of pregnant Saudi associations between obesity and preeclampsia, perineal tears, and episiotomy variables, and other variables reflect no associations. Recommendations: Further studies are needed to generalize the results. This study endorses the pregnant women start the antenatal follow-up from 1st trimester so, the data will be available on the system for research.